2008
DOI: 10.1115/1.2951935
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Fuzzy Adaptive Network in the Modeling of Material Removal Rate in Rotary Ultrasonic Machining

Abstract: Rotary ultrasonic machining (RUM) is one of the cost-effective machining methods for machining difficult to process material. It is a hybrid machining process that combines the material removal mechanisms of diamond grinding with ultrasonic machining. However, due to the lack of understanding of the mechanisms of these operations, models for these machining processes are difficult to establish. In this paper, the support vector fuzzy adaptive network (SVFAN), a parameter free nonlinear regression technique, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The accuracy of the model was demonstrated for magnesia stabilized zirconia. Shen et al [70] developed the model for material removal rate using support vector fuzzy adaptive network (SVFAN) in RUM. Results also compared with that obtained by using fuzzy adaptive network and it had also been showed that the combined approach is a more effective algorithm for the modeling.…”
Section: Rotary Ultrasonic Machiningmentioning
confidence: 99%
“…The accuracy of the model was demonstrated for magnesia stabilized zirconia. Shen et al [70] developed the model for material removal rate using support vector fuzzy adaptive network (SVFAN) in RUM. Results also compared with that obtained by using fuzzy adaptive network and it had also been showed that the combined approach is a more effective algorithm for the modeling.…”
Section: Rotary Ultrasonic Machiningmentioning
confidence: 99%
“…This is the first successful example to use fuzzy control to replace the expert operator. Some of the fuzzy aspects in manufacturing were studied using the proposed adaptive system shen, Pei & Lee, 2004;, Shen, Pei & Lee, 2008Jiao Pei et al, 2005Pai & Lee 1999;shen, et al, 2006;. Industrial welding operation is more art than science.…”
Section: Examples Of Application To Humanistic Systemsmentioning
confidence: 99%
“…Shen et al applied Support Vector Fuzzy Adaptive Network as a parameter-free nonlinear regression technique to model material removal rate. The algorithm retains the advantages of fuzzy adaptive network and support vector machine, and it is a more effective modeling algorithm for complex manufacturing processes [14]. A material removal model for Inconel 718 robotic belt grinding based on acoustic sensing and machine learning is proposed [15].…”
Section: Introductionmentioning
confidence: 99%